2022
DOI: 10.1007/s12144-022-03651-5
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and self-harm in adolescents during the first national COVID-19 lockdown: results from a survey of 10,000 secondary school pupils in England

Abstract: Adolescents’ loneliness and self-harm have received considerable attention during the COVID-19 pandemic with concerns that the socioecological changes taking place would contribute to an escalation of both loneliness and self-harm. However, empirical evidence is scant. We estimated the prevalence of loneliness and self-harm in adolescent school pupils and investigated the association of loneliness and change in loneliness during the UK’s first lockdown with self-harm during lockdown in a cross-sectional school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…The Public Health Report for 2021 argued that in Norway, a large part of the health consequences was likely to be caused by the infection control measures themselves [ 5 ]. For instance, the harm caused to schoolchildren by school closures was a significant worry for many of the DMOs, yet one that could hardly be quantified at the time decisions were made [ 25 , 26 ] [ 5 , 27 – 29 ]. Norway closed all primary-, lower secondary- and upper secondary schools in March 2020 for about 6–8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The Public Health Report for 2021 argued that in Norway, a large part of the health consequences was likely to be caused by the infection control measures themselves [ 5 ]. For instance, the harm caused to schoolchildren by school closures was a significant worry for many of the DMOs, yet one that could hardly be quantified at the time decisions were made [ 25 , 26 ] [ 5 , 27 – 29 ]. Norway closed all primary-, lower secondary- and upper secondary schools in March 2020 for about 6–8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also asked about school-related experiences and activities, including whether they felt a sense of belonging to the school community and how easy they found it to make and keep friends; experiences of school detention, aggressive behaviors, and bullying; and exercise frequency, as well as potential family risk factors, including whether they felt safe in the place they live, food poverty as a proxy for deprivation, and experiences of child abuse. Finally, a few different aspects of mental ill-health were examined, including anxiety and depression measured using the 25-item Revised Children's Anxiety and Depression Scale [48], insomnia measured using the 2-item version of the Sleep Condition Indicator [49], loneliness based on the 3-item version of the UCLA Loneliness Scale [50,51], and lifetime self-harm [52,53]. Full details of the measures used as predictor variables in the study are provided in Table S2 in Multimedia Appendix 1 [48][49][50][51] and the preregistration for this analysis [40].…”
Section: Predictor Variablesmentioning
confidence: 99%
“… 2 Simultaneously, adolescence is additionally a period of high incidences of loneliness among adolescents. A cross-sectional study from England found that 18.1% of adolescents aged 12–18 reported having felt lonely “often” 3 Loneliness is an unpleasant and distressing subjective experience or psychological feeling. 4 , 5 During a lonely state, individuals not only exhibit the subjective state of social isolation, but additionally go through the painful experience of non-acceptance caused by their perception of isolation or lack of contact with others.…”
Section: Introductionmentioning
confidence: 99%
“…48 In consideration, adolescents’ peers and friends are key sources of support for their mental health problems and NSSI. 3 , 49 When adolescents’ social support networks are disrupted, additional risk factors may increase their NSSI and suicidal behavior. 47 In contrast, positive social relationships and social connection may assist them in reducing these behaviors.…”
Section: Introductionmentioning
confidence: 99%